Perlindungan Hukum Terhadap Korban Tindak Pidana Penipuan Yang Dilakukan Oleh Pelaku Usaha E-Commerce Berbasis Transaksi Elektronik - Sanusi, M Fahmi; Ariyanti (MLJ Merdeka Law Journal, 2025)
Currently, online buying and selling transactions require buyers to make upfront payments based solely on product images without knowing the actual condition of the goods. Additionally, various legal issues arise in online transactions, particularly concerning fraud-related crimes. The main challenges in these cases involve aspects of information delivery, communication, and electronic transactions, especially in terms of evidence and legal actions carried out through electronic systems. The difficulty in proving crimes committed electronically results in online fraud victims receiving inadequate legal protection. This study addresses the legal regulations concerning fraud crimes based on electronic transactions in Indonesia, as well as the legal protection for fraud victims committed by e-commerce business operators under the Electronic Information and Transactions Law (UU ITE). The research method used is normative legal research. The findings indicate that fraud crimes, in general, are regulated under Article 378 of the Indonesian Criminal Code (KUHP), which covers actions that unlawfully benefit oneself or others by using a false identity, deceit, or lies to obtain an object, loan, or debt cancellation. Meanwhile, fraud in online transactions is specifically regulated under Article 28, paragraph (1) of Law No. 19 of 2016, which amends Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE). This provision governs the deliberate and unauthorized dissemination of false or misleading information that harms consumers in electronic transactions. Legal protection for victims of fraud in e-commerce is also explicitly regulated under the UU ITE. However, law enforcement officials still rely on the KUHP in handling most cybercrime cases, as the majority of electronic transaction fraud victims are online shop consumers. Legal protection efforts for victims of fraud in online buying and selling transactions can be carried out through both preventive and repressive measures. Keywords: Legal Protection, Fraud Crimes, Business Operators, Electronic Transactions